Mucinous cystic neoplasm of the liver - Navarini, Daniel; Luca Boeira Rovani, André; Benincá Albuquerque, Antônio; Rodriguez, Rubens; Scussel Madalosso, Carlos Augusto (Clinical and Biomedical Research, 2023)
A 55-year-old woman was investigated for occasional epigastric pain and weight loss. T2-weighted abdominal magnetic resonance imaging and magnetic resonance cholangiography revealed a multilocular cyst with multiple septa and a solid component in the liver, measuring 6.1 x 4.8 x 6.5 cm. Given the patient’s symptoms and malignant potential, a laparoscopic segmentectomy with partial resection of segments IV B and V was performed to completely remove the cystic lesion, associated with cholecystectomy. Histopathology demonstrated a cyst lined by columnar mucinous epithelium. Therefore, the diagnosis was mucinous cystic neoplasm of the liver. This article presents a case report and literature review of this entity.